Postural coordination during self-perturbed standing - White, David (University of Ottawa (Canada), 2008)
The central nervous system employs control mechanisms in response to both external perturbations and self-perturbations in order to maintain stable upright stance. Previous studies on self-perturbation tasks involving arm movements have examined postural patterns and the relationship between arm movement and the body's center of pressure: however, the coupling within and between the components of the lower limb have yet to be investigated. To examine these issues ten healthy subjects swung their arms inphase and antiphase in the anterior-posterior direction to a metronome at frequencies of 0.67, 0.75, 1.0 and 1.5 Hz. Our results show differences in the phase relationships, joint amplitudes and sway patterns between inphase and antiphase swinging. These findings provide insight into the existence of separate control mechanisms for the two swinging modes, and therefore highlight task-specific control mechanisms for the lower limbs during self-perturbations.
Keywords: Health Sciences, Recreation.; Biology, Physiology.